WHERE IS ME?: AN EXPLORATION OF VOICE IN L2 WRITING AMONG THAI UNIVERSITY STUDENTS - Thadphoothon, Janpha; Isarankura, Soisithorn (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2024)
The concept of voice in second language (L2) writing is increasingly recognized as a key aspect of language proficiency, though it remains somewhat elusive and controversial. This study aimed to deepen the understanding of voice in L2 writing among 21 Thai university students. We analyzed their responses to questionnaires, including open-ended questions, using basic statistics and content analysis. The data collection took place in January, 2024. Our results revealed that a significant majority of students found writing in English challenging, and their L2 voice differed from their L1 voice. Additionally, their self-reports indicated distinctions between their written and spoken English. Students expressed a loss of confidence and a sense of disconnection from their true selves when tasked with writing in English. Our findings contribute to the literature on L2 voice in writing, confirming that L2 voice in writing is a multifaceted and contextualized construct. We provide practical recommendations for Thai teachers to assist students in developing their L2 voice. Finally, further research is needed to conceptualize Thai students’ voice in English writing.